Discussoo: Towards an intelligent tool for multi-scale participatory modeling. (June 2021) - Anjum, Madiha; Voinov, Alexey; Taghikhah, Firouzeh; Pileggi, Salvatore F.
Abstract: In participatory modeling (PM), a conceptual model emerges from an exchange of information and opinions among stakeholders. This usually happens in a series of in-person workshops restricted to a certain number of attendees during designated time intervals. Our goal is to open up the PM workshop process to engage an unlimited number of participants at various locations, while supporting them with the functionality that the modeling context can offer. We develop a real-time, moderated steering environment, named Discussoo, to facilitate online PM. Users express their opinions about a topic by providing their comments in online discussions. As the discussion evolves, an ensemble of artificial intelligence algorithms in the background automatically produces a dynamic conceptual model to visualize the on-going exchange of opinions. Moderators can use this model to provide feedback to users and guide the discussion. Policymakers and managers can use Discussoo to support more transparent and meaningful engagement of stakeholders. Graphical abstract: Image 1 Highlights: Conventional participatory modelling workshops are restricted in time and in the number of participants. Asynchronous online model development is suggested as a new trend in participatory modelling. Discussoo provides a platform to share opinions and learn from the discussions. This tool can be deployed in any stakeholder engagement process. Discussoo uses AI to automatically elicit group mental models from online discussions.